Social Media Addiction Among Nursing Students and Its Related Factors - Yeşiltepe, Akgün; Demirkiran, Bedriye Cansu; Demir Çam, Sevgi (UI Scholars Hub, 2023)
Background: Social media use has become an indispensable part of our lives as a result of technology advancement and is quite high among students. Methods: This study employed a cross-sectional design. Participants were 289 students from the Faculty of Health Sciences at Artvin Coruh University, Turkey. The Social Media Addiction Scale (SMAS) was used to obtain data. T-test, one-way ANOVA, Pearson’s correlation, and Bonferroni analysis were used to analyze the data. Results: The participants’ mean SMAS score was 81.03 ± 34.79, which was moderate. A weak and positive correlation was found between social media addiction and daily social media use. Statistical differences were found between social media addiction and social class, maternal education level, place of residence, income level, and general health status. Further, statistically significant differences were found between access to social media such as Facebook, Twitter, and Skype, and SMAS and subscales (p < 0.05). Conclusions: The nursing students in this study showed moderate levels of social media addiction. Factors such as daily social media use, year of study, maternal education level, place of residence, income level, and general health status are associated with the degree of social media addiction.